2018
DOI: 10.1002/mus.26188
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of nerve crush injury using adipose‐derived stem cells: A multimodal comparison

Abstract: Animals treated with CR and epineural stem cell injection showed enhanced anatomical and functional recovery. Muscle Nerve 58: 566-572, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
14
2
Order By: Relevance
“… 50 However, significantly higher values in the treated groups point to the benefit of ASC and simple repair in preventing atrophy. 15 , 51 The SSI scores with early single-dose ASC treatment were superior to the results from crush studies with late administration (after 6 weeks), alluding to an immunomodulatory effect of ASC during early phases of neuroinflammation following PNI. 15 Such positive effects were confirmed on nerve histomorphometry, especially nerve fiber density, axon, and myelin area in the ASC-treated group.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“… 50 However, significantly higher values in the treated groups point to the benefit of ASC and simple repair in preventing atrophy. 15 , 51 The SSI scores with early single-dose ASC treatment were superior to the results from crush studies with late administration (after 6 weeks), alluding to an immunomodulatory effect of ASC during early phases of neuroinflammation following PNI. 15 Such positive effects were confirmed on nerve histomorphometry, especially nerve fiber density, axon, and myelin area in the ASC-treated group.…”
Section: Discussionmentioning
confidence: 87%
“… 30 32 While the current body of knowledge supports both trans-differentiation to Schwann cell 33 or paracrine effects via neurotropic and neurotrophic factors 34 36 as possible mechanisms, a combination of both might hold true. 37 , 38 Most studies performed have explored efficacy of ASCs administered locally, 15 seeded in conduits, 8 , 14 , 17 , 39 , 40 or deposited in gels, 41 rather than incorporating ASC-derived neurospheres, exosomes, or conditioned media. 15 , 42 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stem cell transplantation is a very successful treatment modality using tissue engineering in many different diseases. The last two decades of studies have shown the positive effects of various stem cell therapies related to nerve regeneration, in both the central and peripheral nervous system [2,9,10]. It has been shown that the stem cell is differentiated into Schwann cell phenotype and accelerates axonal regeneration and provides better remyelinization [11,12].…”
Section: Introductionmentioning
confidence: 99%